Religious and Medical Pluralism Among Traditional Healers in Johannesburg, South Africa - Galvin, Michael (Journal of religion and health, 2024)
Religion and spirituality are powerful social forces in contemporary South Africa. Traditional Health Practitioners (THPs) are commonly consulted for both spiritual and medical ailments as a first line of care. Many studies have assessed African traditional health seeking behaviors but few have examined beliefs, practices, and behaviors of THPs themselves. This study sought to explore spiritual worldviews among South African THPs. Semi-structured in-depth interviews were conducted with 18 THPs in Johannesburg, South Africa between January and May, 2022. Interviews were transcribed and translated into English. Data were managed using NVivo 12 software and thematically analyzed. The majority of THPs interviewed indicated that initiation as a THP was almost always preceded by a sickness accompanied by dreams/visions that represented an "ancestral calling" to become a healer. Most THPs also trained as both sangomas - who healed according to traditional beliefs - and prophets- who healed according to Christian beliefs. This reflects a syncretic relationship between traditional African beliefs and Christianity. However, not all churches are accepting of traditional beliefs and subsequently these THPs are members only at non-Pentecostal AIC churches who blend both African and Christian practices. Similar to these forms of religious pluralism melding Christianity and traditional beliefs, many THPs also often practice medical pluralism, mixing Western treatments with traditional practices/medicines. THPs are able to adapt elements of Western and African beliefs into healing practices that span multiple religious and medical fields. Thus, collaborative and decentralized healthcare services may be highly acceptable among such a pluralistic community.